Potensi Minuman Probiotik Berbahan Dasar Campuran Buah (Jambu, Lemon, Melon, Bit) Sebagai Minuman Kesehatan - Sari, Afrinia Eka; Anindita, Reza (Jurnal Gizi, 2024)
Background; The health of the digestive tract is very important for maintaining the body's immune system, in maintaining the health of the digestive tract there are two components of probiotics and prebiotics are needed. Probiotics are good bacteria that are beneficial for the health of the digestive tract. Probiotics can be obtained through food or drink that has gone through a fermentation process using gram-positive bacteria. Probiotics produce bacteriocins and several compounds needed by the body such as lactic acid, acetic acid, hydrogen peroxide, lactoperoxidase and lipoperoxide, pyridoxine, niacin, folic acid, cobalamin and biotin which are useful for boosting the body's immune system. Objectives; The purpose of this study was to make a probiotic drink with fruit-based ingredients (guava, lemon, melon, beet) as a probiotic product that can be an alternative health drink. Material and Method; This study used an experimental design with a completely randomized design, where there were three formulas that had differences in the addition of sugar (F1: 10% sugar, F2: 20% and F3: 30%). The materials used in this study included: Guava, Lemon, Melon,Beets, Sugar and used the Lactobacillus plantarum bacterial starter. The tests carried out included: organoleptic test, total plate count test and acidity test Results; the organoleptic test results, it was found that Formula 3 was the most preferred with organoleptic qualities: slightly sour, slightly muddy and very red in color. The red color comes from beets. The acidity level of each formula includes: F1 (3.43), F2 (3.39), F3 (3.34). The results of the total plate number test showed that the average total plate number of the product was 1.7 x 10 8/CFU/ml.Keywords: Beets, Guava, Healthy drink, Lemon, Melon, Probiotics